Geoacoustic inversion techniques utilizing acoustic vector sensors and results from the Monterey Bay Shelf - Guarino, Alexandre Geddes Lemos (2022)
The propagation of acoustic waves in shallow water is affected by the seabed properties. Estimating these properties in situ using acoustics is an area of research that has been in development for decades, and many techniques have been proposed using pressure-only sensors. In recent years, vector sensors have been adopted to expand the capabilities of geoacoustic inversion. This dissertation builds upon the findings of Guarino et al. reported in the Journal of Theoretical and Computational Acoustics and in the Proceedings of the 24th International Congress on Acoustics, 24–28 October 2022. It is shown that the combination of pressure and vertical velocity channels of a vector sensor can improve both the estimation of bottom attenuation coefficient, using the modal phase difference approach, and geoacoustic parameters like sound speed and density, using the multichannel average of dispersion curves. In addition, Time-warping, which is a broadly used technique for modes separation, is improved with the inclusion of a band-pass filter masking approach in the time-frequency analysis. Finally, this work suggests that waveform matching should be used as a preliminary step in dispersion curve analysis to improve inversion performance, or even be the primary choice when a vector sensor is available. The results use data collected in Monterey Bay in 2019.